PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPS KELAS IV SDN 012 LABUHAN TANGGA KECIL KABUPATEN ROKAN HILIR - Rustamini Rustamini; Hendri Marhadi; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The low level of students' understanding of social knowledge learning (IPS) and the achievement of student learning outcomes that are less than the minimum completeness provisions (KKM) that encourage this research conducted. Therefore applied inquiry model to improve student learning outcomes. The type of research used in this research is a classroom action research design (PTK) consisting of 2 cycles, each cycle is done in two meetings in each cycle consisting of four steps: design, observation, and reflection. The instruments used are learning tools and data collection. Based on the result of the research, the improvement of IPS learning outcomes of students IV SDN 012 Labuhan Tangga Kecil Rokan Hilir with the application of inquiry learning model has increased. Can be seen from the average activity of student pre-action student score 64,60 after action in cycle I is 75,0% enough cycle II 89,58% (Good) there is improvement of study activity. Teacher activity also increases in cycle I is 85.42% (Good) to cycle II 93.75% (Very Good). Also can be seen from basic score 94.50% (less) increased to 74.00% enough on UH (Deuteronomy) I and increased lago to 80.25% (good) on UH II.Keywords: Inquiry Model, SDN 012 Labuhan Tangga Keci